Implementasi Jaminan Fidusia Sebagai Jaminan Kredit Usaha Mikro Kecil Menengah (Studi Pada PT. BPR NBP 4 Kisaran) - Pratiwi, Irda; Tanjung, Sivia Mahdalena (PPSDP Undergraduate Journal of Educational Sciences, 2025)
Article 2 paragraph 1 of the Fiduciary Security Law defines fiduciary security as the right to a security interest in movable property, both tangible and intangible, and immovable property, especially those that cannot be encumbered with a mortgage, which remain in the possession of the fiduciary grantor, as collateral for the repayment of certain debts, granting the fiduciary recipient a preferential position over other creditors. Fiduciary security is an accessory agreement of a principal agreement as mentioned in the explanation of Article 6 letter b of the Fiduciary Security Law and must be made with a notarial deed known as the fiduciary security deed. An accessory agreement is born, ends, or is extinguished depending on the main agreement. This legal research uses the empirical legal research method and conducts a case study at the PT. BPR NBP 4 Kisaran Office. This legal research uses primary legal materials, namely: laws. Secondary legal materials, namely: legal books. Tertiary legal materials, namely: non-legal books. The implementation of fiduciary guarantees as collateral for micro, small, and medium enterprise credit at PT. Bank Perkreditan Rakyat Nusantara Bona Pasogit 4 Central Office Kisaran is carried out by collaborating with a third party, namely a notary, for the recording in the form of an authentic deed of the legal act of credit in the form of a fiduciary guarantee deed. The obstacles in the execution of fiduciary guarantees as collateral for credit provision include the loss or damage of the object secured by the debtor, which is not well maintained, leading PT. Bank Perkreditan Rakyat Nusantara Bona Pasogit 4 Central Office Kisaran to take legal action.